Environmental Social Sciences: Methods and Research Design - Jeremy Spoon (Ethnobiology Letters, 2012)
Review of Environmental Social Sciences: Methods and Research Design. Ismael Vaccaro, Eric Alden Smith, and Shankar Aswani, eds. 2010. Cambridge University Press, Cambridge. Pp. 396, 41 b/w illustrations, 20 tables. US$49.99 (paperback). ISBN 9780521125710.